2014
DOI: 10.1007/s11947-014-1442-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Power Ultrasound and Cold Gas-Phase Plasma Treatments on Selected Yeast in Pure Culture

Abstract: High power ultrasound (US) and cold gas-phase plasma (CP) are non-thermal processing technologies that maybe used in food processing industry. The main objective of this research was to study the effect of both treatments on selected yeasts (Rhodotorula spp. 74 and Candida spp. 86) in pure culture. Samples were treated by ultrasound with 57.50-, 86.25-or 115-μm amplitude, for 3, 6 or 9 min at 20°C, and 40 or 60°C in the case of thermosonication. For cold gas-phase plasma treatments, samples were treated at a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Recently, our results showed influence of cold plasma on food decontamination (Herceg, Režek Jambrak, Vukušić, Stulić, Stanzer, & Milošević, 2015;Režek Jambrak, Vukušić, Stulić, Mrvčić, Milošević, & Herceg, 2014), and other authors confirmed suitability for use with fruit juices (Shi, Zhang, Wu, Li, Ma, & Shao, 2011;Surowsky, Frohling, Gottschalk, Schluter, & Knorr, 2014). Furthermore, our research group proposed that non-thermal plasma can be used for pasteurization in fruit juice production (Elez Garofulić, Režek Jambrak, Milošević, Dragović-Uzelac, Zorić, & Herceg, 2015).…”
Section: Introductionsupporting
confidence: 64%
“…Recently, our results showed influence of cold plasma on food decontamination (Herceg, Režek Jambrak, Vukušić, Stulić, Stanzer, & Milošević, 2015;Režek Jambrak, Vukušić, Stulić, Mrvčić, Milošević, & Herceg, 2014), and other authors confirmed suitability for use with fruit juices (Shi, Zhang, Wu, Li, Ma, & Shao, 2011;Surowsky, Frohling, Gottschalk, Schluter, & Knorr, 2014). Furthermore, our research group proposed that non-thermal plasma can be used for pasteurization in fruit juice production (Elez Garofulić, Režek Jambrak, Milošević, Dragović-Uzelac, Zorić, & Herceg, 2015).…”
Section: Introductionsupporting
confidence: 64%
“…However, there is a need to observe formation of free radicals upon nonthermal processing of food products to observe current production of free radical that can have influence on oxidation of nutritive compound. There are some researches and review papers that are mentioning formation of free radicals upon nonthermal food processing (Barba et al., 2020; Misra et al., 2018; Nutrizio et al., 2020; Tresp et al., 2013), and that formation is connected to inactivation of microorganisms (Jambrak et al., 2015). However, extended processing can lead to increased formation of free radicals that will rapidly interact with organic compound and lead to deterioration of food (Režek Jambrak et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cold atmospheric plasma has been already shown to be highly efficient at microbial inactivation Režek Jambrak et al, 2014). The concept of applying cold-plasma to enhance the shelf-life of fresh/freshly-prepared food is new and there is scarce information about the interactions of energetically highly reactive plasma species with phytochemical compounds (Grzegorzewski, Ehlbeck, Schlüter, Kroh, & Rohn, 2011).…”
Section: Introductionmentioning
confidence: 99%